Changing male perceptions of gender equality: Evidence from an experimental study - Cuong Viet Nguyen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Reducing gender inequality is a critically important development challenge, especially in countries with widespread and deep-rooted prejudices against women. In this study, we use a randomized control trial to examine whether facilitating Vietnamese men to reflect about gender equality can reduce their gender bias. We randomly selected two groups of husbands and requested one group to make comments on gender-related laws and another group to write stories about gender equality. We find that commenting on gender-related laws reduces men's bias against women slightly, while writing stories has a strong effect on reducing existing prejudice against women. Moreover, writing gender-related stories improves men's knowledge of gender-related laws. Nonetheless, there is only a small effect of this treatment on doing housework. Changing men's behaviour in practice requires stronger, more sustained interventions.
Keywords: J16; K38; D91; C93; 330; gender inequality; male perception; experimental design; women empowerment; cognitive dissonance